Eu sou artivista: the impact of digital art in the awareness of Portuguese young adults - Correia, Cátia Inês Batista (2022)
The development of new technologies and the creation of the internet have changed the way humanity behaves and lives everyday life. Social networks, made popular in the recent past, are nowadays part of the routine of a high percentage of the world population, mainly in developed countries. They have therefore become one of the main means of communication, not only between humans at a distance, but also in the dissemination of information to the masses, in some cases replacing television, magazines and newspapers, which have also transitioned to digital form throughout the years. The digital world thus allows for a transformation in the way citizens practice activism and how they organize to protest. This report intends to assess the situation allowed by the development of social networks as a space of freedom to express opinions. The Eu Sou Artivist project aims to assess how this range of possibilities on social networks impacts (positively or negatively) the practices of social intervention and what is the role of digital art in an attempt to spread awareness and information, encouraging more active Portuguese youth in society and in Portuguese political life.